PENGARUH PROMOSI, FASILITAS, DAN DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG DI WISATA KAMPOENG DJAWI JOMBANG - Putri, Karlinda Anika Rigita; Mulyati, Awin; Mulyati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2021)
ABSTRACTThis research conducted by the author with the titled The Effect of Promotion, Facilities, and Travel Attractions on Visiting Decisions. The author takes the tourism destination in  Kampoeng Djawi Jombang.Kampoeng Djawi  is a tourist destination in  Jombang city which seeks to bring up and introduce Javanese models of old days. Kampoeng Djawi Jombang was established in 2013. This tour has 5 clusters, each of which has its own characteristics.This study aims to find out and analyze how the influence of Promotion, Facilities, and Tourism Attraction on Visiting Decisions  The population in this study are visitors who will visit Kampoeng Djawi Jombang Tourism.The results showed that promotion and facilities had a positive and significant effect on the Visiting Decision, while the Attraction of Tourism did not significantly influence the Visiting Decision on the Kampoeng Djawi Jombang Tourism. This is because the Attractions of Kampoeng Djawi such as the type of performances that are less attractive and inadequate lodging in Kampoeng Djawi Jombang. In this study it is also known that the Visit Decision is influenced by the variable Promotion, Facilities, and Travel Attraction by 30.9% while the remaining 69.1% is influenced by variables or other factors not examined in this study such as Location, Ticket Prices, Quality Services and so on.